LONG-TERM FOLLOW-UP OF PATIENTS WITH RETINITIS PIGMENTOSA TYPE 12 CAUSED BY CRB1 MUTATIONS: A Severe Phenotype With Considerable Interindividual Variability. Issue 1 (January 2017) - Mathijssen, Inge B.; Florijn, Ralph J.; van den Born, L. Ingeborgh; Zekveld-Vroon, Renate C.; ten Brink, Jacoline B.; Plomp, Astrid S.; Baas, Frank; Meijers-Heijboer, Hanne; Bergen, Arthur A. B.; van Schooneveld, Mary J.
Abstract : Purpose: To examine the long-term clinical course and variability in a large pedigree segregating CRB1 type autosomal recessive retinitis pigmentosa. Methods: An observational case study of 30 patients with CRB1 type autosomal recessive retinitis pigmentosa, homozygous for the CRB1 c.3122T > C; p.(Met1041Thr) mutation from a Dutch genetically isolated population in which the CRB1 gene was originally identified. The authors evaluated medical records, analyzed a questionnaire, and performed a comprehensive ophthalmic examination, including optical coherence tomography. Results: Mean follow-up was 19 years (range 0–45 years, SD 15 years). With aging, patients showed progressive visual decline, deterioration of visual fields, increasing narrowing of the anterior chamber, increased prevalence of cataract, and an increase in the amount of intraretinal pigmentations. Fifty percent of patients had a visual acuity of ⩽0.3 at Age 18 and of ⩽0.1 at Age 35. Electroretinogram responses were severely reduced or absent already at a young age and optical coherence tomography showed increased retinal thickness with often cystoid maculopathy at young age, and thinning of the retina and disorientation of the photoreceptor layer in the late stages. The clinical course showed considerable interindividual variability, but intraindividual similarity between both eyes was the rule. Conclusion: The wide and variable clinical spectrum in patients with the same CRB1 mutation supports the hypothesis that the CRB1 type autosomal recessive retinitis pigmentosa–phenotype is modulated by other factors. The clinical variability will make it harder to evaluate the effect of (upcoming) therapies for retinitis pigmentosa, although because of the intraindividual similarity between both eyes, the contralateral eye can be used as an excellent internal control. Abstract : Study of the long-term clinical course and variability in a large pedigree segregating CRB1 type autosomal recessive retinitis pigmentosa(RP12). Clinical variability is wide, supporting the hypothesis that the phenotype of patients with CRB1 mutations is modulated by other factors. This complicates the evaluation of the effect of (upcoming) therapies for retinitis pigmentosa type 12.